Quality of life in patients in South Korea requiring special care after fixed implants: a retrospective analysis - Soo-Yeon Yoo; Hyun-Jong Kim; Seong-Kyun Kim; Seong-Joo Heo; Jai-Young Koak; Ji-Man Park (BMC, 2023)
Abstract Background The study on oral health-related quality of life (OHRQoL) of disabled patients is rare but critical for welfare of patients. The aim of this study was to examine the effect of fixed implants in edentulous areas on OHRQoL in Korean disabled patients. Methods The OHRQoL of 63 disabled individuals was evaluated using the Oral Health Impact Profile (OHIP)-14 questionnaires and studied by potential affecting variables such as age, sex, disability severity, and time of disability acquisition. Wilcoxon-signed rank tests were used to examine the OHIP-14 scores for those who had pre/post-fixed implants. Multiple linear regression analysis was used to examine the relationships between factors and OHIP-14 scores before and after implants. A partial correlation analysis was also performed to determine which variables influenced OHIP-14 scores before and after treatment. The Mann-Whitney test was employed for sex and time of disability acquisition analysis (α = 0.05). Results Significant improvement was found in OHIP-14 post-implant treatment scores (P < .001). After implant treatment, the severity of disability produced significantly different results (P = .009). Pearson's correlation coefficient between severity of disability and pre/post-implant OHIP-14 scores was 0.265 (P = .030). After controlling for severity of disability, the results showed older patients had lower OHIP-14 scores (P = .032). No differences were found for sex or time of disability acquisition (congenital vs. acquired). Conclusions Fixed implant treatment improved OHRQoL for disabled patients, and the severity of disability was positively correlated with improvement of OHRQoL. For patients with a similar level of disability, the OHRQoL decreased with age.